Climate change and children (UNICEF New YorkUS, 2007)
Presents a summary of comments and letters from children and young people from all over the world collected from UNICEF Voices of Youth, child delegates to the 2007 UNEP African Regional Children's Conference on the Environment and the 2007 World Scout Jamboree in cooperation with UNDP.
Keywords: CLIMATE CHANGE